2017
DOI: 10.1007/s12119-017-9407-0
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Millennials and Intersex Awareness

Abstract: This paper investigates the awareness, attitudes, and opinions of Japanese millennials about intersex people. This research attempts to fill a gap in extant literature concerning the intersex in Asia via an exploratory analysis. The LGBTQ(I) discourse of Japan mimics that of the west; often the "I" is totally disregarded. Here, a snapshot of Japanese millennial awareness is offered using survey results collected from a convenience sample of Japanese college students. Findings suggest that the understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Furthermore, our overall findings suggest that even though intersex variations present a clear challenge to the idea that all those falling outside the binary definition of sex and gender choose to do so, it is still associated with deviant gendered behavior in some way. Yet, much like the Japanese sample analyzed by Lusk (2017), this study revealed more acceptance of intersex variation than homosexuality. In fact, 75.2% of the sample overall felt that people with intersex variations should “ be allowed to marry whomever they please ,” compared to 67.1% for homosexual individuals.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, our overall findings suggest that even though intersex variations present a clear challenge to the idea that all those falling outside the binary definition of sex and gender choose to do so, it is still associated with deviant gendered behavior in some way. Yet, much like the Japanese sample analyzed by Lusk (2017), this study revealed more acceptance of intersex variation than homosexuality. In fact, 75.2% of the sample overall felt that people with intersex variations should “ be allowed to marry whomever they please ,” compared to 67.1% for homosexual individuals.…”
Section: Discussionmentioning
confidence: 57%
“…The Haynes definition was selected in an effort to replicate the instrument used in a previous study on intersex variation, drawn from a sample of non-native English speakers with little familiarity with intersex variation (Lusk, 2017): “‘Intersex’ means someone who is born with biological traits that make it hard to determine whether they are conclusively male or female (Haynes, 1999). This could mean some variance of chromosomes beyond the dichotomous 46XX or 46XY, abnormal hormone balance, or difference in appearance of genitalia.” (Lusk, 2017, p. 619)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7. It should be noted that this is based on a small sample of 239 students at Miyazaki International College, Miyazaki City, with an n of 153; see Lusk (2017). 8.…”
mentioning
confidence: 99%